Working with Communities to Improve Dignity: The Case of Improved Bio-Centres in Kenya - (:unkn) unknown (My University, 2011)
This article presents the bio-centre technology, an innovative solution that addresses the fundamental needs of densely populated informal settlements, which has improved sanitation and energy access options for residents. The bio-centre technology not only arrests the myriad of health, social and environmental problems associated with poor disposal of human waste but it also reduces the energy burden of poor communities as well as introducing new opportunities for income generation and positive socialization amongst the inhabitants in the catchment area of the facility. This article discusses the sanitation challenges in informal settlements and the bio-centre initiatives, of community actors, to redress the attendant problems.
Keywords: African Research